Protective function of the voltage-gated potassium channel Kv11.3 in a mouse model of cardiac ischemia/reperfusion injury - Hayato Sasaki; Kazuki Otake; Kazuki Takeda; Karin Tesaki; Eiki Takahashi; Jumpei Yasuda; Shizukaze Matsuda; Ayumu Kawasaki; Masaki Watanabe; Kosuke Otani; Muneyoshi Okada; Masakazu Sekijima; et al. (PLoS ONE, 2025)
Voltage-gated potassium (Kv) channels contribute to repolarization in excitable tissues such as nerves and cardiac muscle; consequently, they control the firing frequency and duration of action potential. Their dysfunction can thus cause neurological disorders and cardiac disorders with arrhythmias. The dysfunction of Kv11.3 is associated with bipolar disorder, but no reports have linked it to heart disease. Kv11.3-knocked out (KO) mice exhibit behavioral abnormalities, but they do not have cardiac abnormalities. Ischemia–reperfusion (I/R) experiments were performed on the hearts of Kv11.3 KO mice to determine whether they would differ from wild-type mice when exposed to stimuli that could induce sudden cardiac death. The mortality rates and infarct size of the Kv11.3 KO mice increased after cardiac I/R. The corrected QT interval was shortened in the wild-type mice after cardiac I/R, but it remained nearly unchanged in Kv11.3 KO mice with alterations in heart rate variability. These phenotypes could be reproduced by administering high-dose NS-1643, a Kv11.3 channel antagonist, after cardiac I/R. The infarct size had no significant difference in the ex vivo cardiac I/R experiment in contrast to the in vivo cardiac I/R experiment. Our study indicated that Kv11.3 protects the myocardium from I/R injury through neural pathways.